Women Disassembling Silent Diplomacy of Beijing+20 & New York CSW59: a Study of Woman-Friendly International Diplomacy - Kholifah, Dwi Ruby (Jurnal Perempuan, 2015)
This paper examines a comprehensive picture of women’s advocacy in Beijing+20 and Commission on the Status of Women 59 New York that spoke against silencediplomacy led by Indonesian government. Indonesia was seen as most democratic Muslim country in the World by the UN. Yet Indonesia was not promoting works in human rights maximally, especially the advancement of women’s rights and children’s rights. Women’s Movement to advocate the previous two international meetings had successfully opened-up a more women-friendly advocacy to advance status of women and children under international gender instruments.